Synthesis and Antibacterial Activities of 1,2,3,4,6,7,8,9,10-Nonahydro-1,3,7,9,10-Pentaphenyl- 5-(2-Furanyl)-2,8-Dithio-4,6-Dioxo-5H-Pyrido [2,3-d; 6,5-d´ ] Dipyrimidine - Nandha Kumar, R.; Suresh, T.; Mohan, P.S. (Asian Journal of Chemistry, 2010)
Biologically potent pyrido dipyrimidines have been achieved from 1,3-diary1-2-thio barbituric acid with furfural and aniline. The spectral and analytical data support the structure of the synthesized compounds and all the compounds were screened for their antibacterial activities against Enterobacter faecalis and Aeromonas hydrophilla.